Eksperimen Pencampuran Warna Dalam Meningkatkan Keterampilan Sains Pada Anak Usia Dini - Mulyani, Ani (CV. ITTC INDONESIA, 2024)
This research, conducted by Saya Ani Mulyani, aims to optimize the use of simple science experiments, especially in the context of color mixing, to increase learning creativity in young children. The research method used is qualitative research. The participants in this research were 14 children aged 4-5 years from an early childhood education institution. The intervention was carried out in the form of a simple science experiment involving mixing primary colors. Data was collected through participant observation during the intervention, interviews with teachers, and reflective notes. Data analysis was carried out using a qualitative approach in Kober At-Taubah, Kp. Ciawitali, Pasanggrahan Village, District. Sukawening, Kab. Garut, West Java. The research results show that the use of simple science experiments in early childhood learning can increase their learning creativity. Children show a high interest in experimental activities, as well as the ability to generate new and creative ideas in exploring color mixing. Additionally, interaction between children also increases, allowing them to learn from each other and develop their social skills. These findings highlight the importance of using interesting and experience-based learning approaches in developing creativity in early childhood. The practical implication of this research is the need to integrate simple science experiments into the early childhood education curriculum as a means of stimulating PAUD creativity.